2018
DOI: 10.3389/fmicb.2018.01087
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa L10: A Hydrocarbon-Degrading, Biosurfactant-Producing, and Plant-Growth-Promoting Endophytic Bacterium Isolated From a Reed (Phragmites australis)

Abstract: Bacterial endophytes with the capacity to degrade petroleum hydrocarbons and promote plant growth may facilitate phytoremediation for the removal of petroleum hydrocarbons from contaminated soils. A hydrocarbon-degrading, biosurfactant-producing, and plant-growth-promoting endophytic bacterium, Pseudomonas aeruginosa L10, was isolated from the roots of a reed, Phragmites australis, in the Yellow River Delta, Shandong, China. P. aeruginosa L10 efficiently degraded C10–C26 n-alkanes from diesel oil, as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 59 publications
3
64
0
3
Order By: Relevance
“…Endophytic Serratia marcescens strain MSRBB2 was reported to produce prodiginines and serratamolides and was evaluated on it biosynthetic pathway with biochemical analysis of feeding experiments (Eckelmann et al, 2018). Prodiginines produced naturally by microorganisms are group of tripyrrole alkaloid which has wide bioactivity, including antibacterial, antiprotozoal, and antifungi (You et al, 2019). This also indicated that the antibacterial activity of bacterial endophytes from mangrove leaves in this study may due to the production of secondary metabolites such as prodiginines.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Endophytic Serratia marcescens strain MSRBB2 was reported to produce prodiginines and serratamolides and was evaluated on it biosynthetic pathway with biochemical analysis of feeding experiments (Eckelmann et al, 2018). Prodiginines produced naturally by microorganisms are group of tripyrrole alkaloid which has wide bioactivity, including antibacterial, antiprotozoal, and antifungi (You et al, 2019). This also indicated that the antibacterial activity of bacterial endophytes from mangrove leaves in this study may due to the production of secondary metabolites such as prodiginines.…”
Section: Discussionsupporting
confidence: 56%
“…Pseudomonas also has great potential on producing antibiotic bioactive potential such as indole derivatives, phenazines, pyrrolnitrin-type antibiotics, glycolipids, another substances (Pratiwi et al, 2017). Wu et al (2018) evaluated P. aeruginosa L10 as biosurfactant producing and excellent hydrocarbondegrading bacteria isolated from roots, stems and leaves of a Reed Phragmites australis).…”
Section: Discussionmentioning
confidence: 99%
“…Under the presence of compatible microbes in the plant system, fine-tuning takes place in the hormonal balance that leads to better plant growth, development, and reproduction even under pathogenic stresses [38,39,42,43]. Among rhizospheric and endophytic plant growth-promoting bacteria, Pseudomonas aeruginosa is the most studied and successful plant symbiont conferring resistance against a wider range of plant pathogens by direct antagonism or by triggering systemic resistance [44,45]. P. aeruginosa has adapted to a wide ecosystem and plays a major role in plant health [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…It colonizes rhizospheric soil, roots, and in some cases aerial parts of the plant. It can even grow as endophytes [45,[47][48][49]. P. aeruginosa is an excellent endo-symbiont and has myco-parasitic ability, protecting plants directly from pathogen attack, and it is well known for its ability to stimulate plant growth and development [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they identified genes related to PHs degradation, such as putative genes encoding monooxygenase, dioxygenase, alcohol dehydrogenase, and aldehyde dehydrogenase. Genome annotation revealed that P. aeruginosa L10 contained a gene cluster involving in the biosynthesis of rhamnolipids, rhlABRI, which could be responsible for the observed biosurfactant activity [69].…”
Section: Discussionmentioning
confidence: 99%